Dietary supplementation of composite feed additive reduces enteric methane production and enhances feed efficiency, milk production and immunity in Murrah buffalo (Bubalus bubalis) - Avijit Dey; Shyam S. Paul; Satbir S. Dahiya; Ashok K. Balhara; Jerome Andonissamy; Balbir S. Punia; Yendrembam M. Chanu (Revista Científica)
Buffalo plays a fundamental role in the livelihood of peo ple of Asian countries by providing milk, meat, draught power, and dung. Asia is home to more than 90% of the world’s buffalo population, out of which South Asian countries harbor about 78% of buffaloes. India ranks first in the world’s total milk production, where about 50% of milk is contributed by 108.9 million total buffaloes, 57% of the global buffalo population. At the same time, buffaloes are one of the country’s most significant contributors to greenhouse gases. Therefore, the objective of the present study was to develop a rumen-balanced composite feed additive (RESMI) for reducing enteric methane production and improving health and production performances in buffaloes. The present research involved a series of in vitro, in sacco, and in vivo experiments in growing (n=24) and milking buffaloes (n=18). The feed supplement was developed at the institute, composed of an ideal combination of methane inhibitors, alternate hydrogen sinks, and some rumen-stimulating agents (Indian Patent Grant No. 388717 dated 08.02.2022) and its efficacy examined through a series of in vitro experiments. A completely randomized design was used to analyze the experimental data. Supplementation of RESMI (@ 2.5% of feed intake.) was found to reduce methane emission (p<0.05) by reducing the number of methanogenic archaea in the rumen and promoting the growth of alternate hydrogen utilizers like sulfate-reducing bacteria. The feed additive stimulated the rumen ecosystem by increasing microbial fibrolytic activity. It thus increased (p<0.05) fiber digestion, reducing the rate of ammonia production in the rumen with concomitant improvement in feed utilization and performance of buffaloes, resulting in an increase in the growth rate by 10%, feed conversion efficiency by 15% and milk production by 10.4%. The results revealed increased digestibility of nutrients, especially crude fiber, with decreased (p<0.05) methane concentration in the exhaled air of lactating buffaloes. The health status regarding cell-mediated and humoral immune response was also enhanced (p<0.05) in supplemented buffaloes. The feed supplement RESMI significantly reduced enteric methane production from buffaloes and lowered environmental pollution from ruminant production systems. A discernible positive impact on growth, milk production, and immunity status was evident in supplemented buffaloes.